Synthesis, characterization, pharmacological and computational studies of 4, 5, 6, 7-tetrahydro-1, 3-benzothiazole incorporated azo dyes - Maliyappa, M. R.; Keshavayya, J.; Mallikarjuna, N. M.; Krishna, P. Murali; Shivakumara, N.; Sandeep, Telkar; Sailaja, Krishnamurty; Nazrulla, Mohammed Azeezulla (Journal of Molecular Structure, 2019)
The present work describes the synthesis of five novel heterocyclic azo dyes (4a-4e) through conventional diazo-coupling reaction of 4, 5, 6, 7-tetrahydro-1, 3-benzothiazole with various coupling compounds at 0-5 degrees C. The chemical structures of the synthesized azo dyes were characterized by both theoretical and experimental techniques. All the synthesized molecules were evaluated for their antioxidant activity by two different techniques such as DPPH and FRAP. The results indicated that all the synthesized compounds proved to be potent antioxidants. The anti-mycobacterial activity of the azo dyes was tested against M. tuberculosis and the compounds 4a and 4e showed higher activity among the tested dyes. The DNA binding studies showed effective intercalation properties between the azo dyes and CT-DNA. Finally, the molecular docking studies indicated a possible interaction of the azo dyes with target receptor RpsA. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Azo dyes; Benzothiazole; CT-DNA; DFT; tuberculosis

Theoretical study on cyclophane amide molecular receptors and its complexation behavior with TCNQ - Sundaram, Soma Sundaram Meenakshi; Karthick, Selvam; Sailaja, Krishnamurty; Karkuzhali, Rajendran; Gopu, Gopalakrishnan (Journal of Photochemistry and Photobiology B-Biology, 2020)
Complexation behavior of cyclophane amide molecular receptors towards 7,7,8,8-tetracyanoquinodimethane (TCNQ) studied. TD-B3LYP/6-31 + G(d,p) based density functional theory was employed to investigate the photophysical characteristics of the complexes obtained. Syn isomers of cyclophane amide molecular hosts show preferred conformation over other conformations. Molecular Orbital analysis indicates the electronic structure change, which reflects in the absorption spectra of the cyclophane amide-1@TCNQ, and cyclophane amide-2@TCNQ charge-transfer (CT) complexes. Binding energy studies with B3LYP-D3/6-31 + G (d,p) theory demonstrated that the more effective binding of the pyridine-2,6-dicarboxamide macrocycles than for their isophthalamide analogs. Both the CT complexes show intermolecular bifurcated hydrogen bonding (N-H-(host)center dot center dot center dot N-(guest)center dot center dot center dot H-N-(host)) interactions (2.06 to 2.08 angstrom), and pi((host))center dot center dot center dot pi((guest)) interactions (3.2 to 3.4 angstrom). Calculated BSSE corrected complexation energy (Delta E) be associated with the formation of the inclusion complexes in the range - 28 to similar to 37 kJ mol(-1), indicating spontaneity of host-guest complex formation in both the cases. From the calculated vibrational spectra of these complexes, the formation of inclusion complexes via N - H-(host)center dot center dot center dot N-(guest) and pi((host))center dot center dot center dot pi((guest)) intermolecular interactions established by the frequency shift in the N - H vibrations. Mulliken population analysis performed to recognize the CT process and the variation in charges between the free and complex TCNQ molecules suggests the intermolecular charge transfer. This study indicates that these cyclophane amides can be a decent CT complexation host for the guests like TCNQ.
Keywords: Absorption; Charge transfer complex; Cyclophane amides; Electrostatic potential surface; Host-guest; Molecular orbitals; Time-dependent density functional theory